2018
DOI: 10.30919/es8d622
|View full text |Cite
|
Sign up to set email alerts
|

Spray Pyrolytic Deposition of Zirconium Oxide Thin Films: Influence of Concentration on Structural and Optical Properties

Abstract: Zirconium oxide (ZrO ) thin films were deposited by spray pyrolysis technique using precursor solution of zirconyl chloride octahydrate 2 o (ZrOCl .8H O) on glass substrate at 450 C. The effects of concentration of precursor solution on the structural and optical properties of ZrO 2 2 2films were investigated. The films were characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Energy-dispersive Xray spectroscopy (EDX), Transmission electron microscopy (TEM), UV-vis analysis and Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…31 Among all these catalysts, the metal oxides and their nanocomposites came into spotlight owing to their low band gap, non-toxicity, cost-effectiveness, high chemical stability, easy availability, and good electrical conductivity. 32,33 Currently, the mono metal oxides have been explored often for the sensing application, including, W 18 O 49 , 27 CuO, 34,35 SnO 2 , [36][37][38] ZnO, [39][40][41] In 2 O 3 42 a-NiMoO 4 , 43,44 ZrO, 45 NiO, 46,47 50,51 and CdO. 52 Amongst these transition metal oxides, NiO is a good electro-catalytic material for sensing applications of alcohol since it is p-type semiconducting material having good chemical/thermal stability and catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…31 Among all these catalysts, the metal oxides and their nanocomposites came into spotlight owing to their low band gap, non-toxicity, cost-effectiveness, high chemical stability, easy availability, and good electrical conductivity. 32,33 Currently, the mono metal oxides have been explored often for the sensing application, including, W 18 O 49 , 27 CuO, 34,35 SnO 2 , [36][37][38] ZnO, [39][40][41] In 2 O 3 42 a-NiMoO 4 , 43,44 ZrO, 45 NiO, 46,47 50,51 and CdO. 52 Amongst these transition metal oxides, NiO is a good electro-catalytic material for sensing applications of alcohol since it is p-type semiconducting material having good chemical/thermal stability and catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Control of morphology, and consequently the material surface, has a great influence on the physicochemical properties of the materials and serves as a powerful way to modulate the functional properties. To the best of our knowledge, there has been no comprehensive experimental work, supported by theoretical simulations, specifically dealing with surface-dependent sensor and magnetic properties of ZnFe 2 O 4 materials. Inspired by these reports, we aim to bridge the knowledge gap between theoretical and experimental results by preparing ZnFe 2 O 4 NPs with different exposed surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that there may be potential applications in the field of electromagnetic protection in the future by the excellent electromagnetic wave absorption properties of carbon nanotubes. [ 16–18 ] Some studies have shown that many metal oxides such as ZnO, [ 19–22 ] CuO, [ 23 ] NiO, [ 24 ] Fe 2 O 3 , [ 25 ] ZrO 2 [ 26 ] are widely used in various fields as a result of their unique properties. [ 27–31 ] Among them, Al 2 O 3 ceramic particles can effectively improve the strength of copper matrix composites due to their high hardness and wear resistance.…”
Section: Introductionmentioning
confidence: 99%